Antidiabetic activity of Coriandrum sativum in streptozotocin induced diabetic rats - Das, Sayan; Chaware, Sanjeevani; Narkar, Nimish; Tilak, Abhijeet V.; Raveendran, Siddhi; Rane, Pratik (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes mellitus (DM) can be defined as chronic hyperglycemia due to lack in insulin secretion and/or action. This study was designed to compare the antidiabetic activity of Coriandrum sativum L. with the standard antidiabetic drug, Metformin in Streptozotocin induced diabetic rats. Methods: Streptozotocin (STZ) was used to induce diabetes in the rats. Standard drug was metformin and test drug were Coriandrum sativum seed extract. 4 groups of 8 rats each were taken (normal control, diabetic control, streptozotocin + Coriandrum sativum and streptozotocin + metformin). Blood Sugar Levels (BSL) and HbA1C levels were estimated on day 0, 14 and 28 and day 28 respectively. Results: Streptozotocin administration resulted in significant rise in BSL. This rise was reduced with the administration of CS seed extract, but the reduction was more with chronic administration. It also reduced the HbA1C levels but couldn’t attain total normoglycemia. However, the reduction of BSL was superior with Metformin compared to the test drug. Conclusions: Oral administration of Coriandrum sativum seed extract at a dose of 40 mg/kg has shown antihyperglycemic activity in streptozotocin induced diabetic rats. Thus, Coriandrum sativum may have considerable therapeutic benefit as an antidiabetic agent and can be suggested as a potential dietary add on.